Visual Quality Protection of Ciboer Rice Fields to Maintain the Attraction of Bantar Agung Tourism Village - Ray March Syahadat; Priambudi Trie Putra; Ismail Saleh; Tandri Patih; Anendawaty Roito Sagala; Dimas Muhammad Thoifur (AGRARIS: Journal of Agribusiness and Rural Development Research, 2021)
Bantar Agung Village in Majalengka Regency, West Java Province, is developing agriculturally-based tourism. The Ciboer Rice Fields area is one of the attractions in the village of Bantar Agung that presents the visual beauty of the rice field landscape. New agrotourism opportunities will be developed in this area. The study has aimed to evaluate the visual quality of the Ciboer Rice Fields and how it would be affected by agrotourism-related changes. Data were analyzed using Kendall’s W test, scenic beauty estimation (SBE), semantic differential (SD), factor analysis, and multidimensional scaling (MDS). It is found that when more objects are added to the Ciboer Rice Fields landscape, the value of beauty is diminished. Village regulations are needed to protect the visual experience of the Ciboer Rice Fields.